Analysis of determination bad nutrition status in the UPT Puskesmas of Lam village, Sei Lepan Langkat district - Nicko Agung Sutisna; Liani Liani; Sri Lestari Ramadhani Nasution (Sean Institute, 2024)
Prolonged malnutrition in children can reduce productivity, physical growth, work capacity and reproductive performance in adulthood. The causes of malnutrition are very complex, so handling malnutrition problems requires a comprehensive approach. The aim of the research is to analyze the determination of malnutrition status at the UPT Puskesmas Desa Lama, Sei Lepan District, Langkat Regency in 2023. Type and research design, quantitative descriptive methodwith a cross sectional approach. Research location inUPT Puskesmas Lama Village, Sei Lepan District, Langkat Regency in January-February 2024. The research population was 35 parents of malnourished babies, total sampling technique, total sample of 35 people. Univariate and bivariate analysis with chi square. Research resultThere is no relationship between nutritional status and mother's knowledge with a p value of 0.101 > 0.05, there is a relationship between nutritional status and parental income with a p value of 0.003 < 0.05, there is a relationship between nutritional status and toddler eating patterns with a p value of 0.000 < 0 .05.